Influence of Stacking Sequence on Mechanical and Metallurgical Properties of Ramie/areca Laminates Using B4C Nano Filled Epoxy Resin. Issue 10 (3rd October 2022) - Vijayan, D; Thiagarajan, Rajmohan
ABSTRACT: The areca fibers are significantly playing a vital role in the production of activated carbon, ethanol, and enzyme, as a fuel in bio-gas and commonly used as air fresheners. Due to hydrophilic in nature of areca fibers exist nonpolar characteristics and compounding difficulties along with the matrix result an ununiform distribution of resins which increase complexity issues while laminating into the desired shape. Moreover, an uneven resin flow caused fibers to de-bond from the laminated surface that consequences low mechanical and metallurgical properties. Therefore, an attempt has been made to utilize ramie fiber as an effective compatibilizer for the areca fiber. The necessary tests, such as mechanical and metallurgical characteristics of areca/ramie fibers were analyzed by varying its stacking sequences. Moreover, B4 C nanoparticles were dispersed on the fibril surfaces to understand the effects of nanoparticles on the areca/ramie fibers. The obtained results revealed that ramie fibers could be used as a better compatibilizer to retain the required shape and also to produce an adequate bonding between the fiber/matrix.